GC-MS ANALYSIS OF SOME BIOACTIVE COMPONENTS IN THE ROOT EXTRACT OF IXORA COCCINEA LINN - NORLIANA GHAZALI,; NURUL ASMA ABDULLAH,; ASIAH ABU BAKAR,; NOOR KHAIRIENA MOHAMAD, (International Journal of Pharma and Bio Sciences, 2014)
Ixora coccinea Linn is commonly known as jungle of geranium and red ixora found throughout India. In addition, the flowers, leaves, root and stems of Ixora coccinea Linn are used to treat various ailments in the Indian traditional system of medicine, the Ayurveda and also in various folk medicines. In the current study, the methanolic extract of Ixora coccinea Linn root has been subjected to GC-MS analysis. Seventeen chemical constituents have been identified, the major chemical constituents are n-Hexadecanoic acid (7.38 %), 9-Octadecenoic acid, Methyl-ester (1.97), Phenol, 2,6-dimethoxy (1.35 %), 13-Docosenamide (1.31%), Phenol, 3,4,5-trimethoxy (1.24 %), 4, 8, 12, 16-Tetramethylheptadecan-4-olide (1.13 %).